Intraoperative use of remifentanil and opioid induced hyperalgesia/acute opioid tolerance: systematic review - Kim, Sang Hun; Stoicea, Nicoleta; Soghomonyan, Suren; Bergese, Sergio D. (Frontiers in Pharmacology, 2014)
Introduction The use of opioids has been increasing in operating room and intensive care unit to provide perioperative analgesia as well as stable hemodynamics. However, many authors have suggested that the use of opioids is associated with the expression of acute opioid tolerance (AOT) and opioid-induced hyperalgesia (OIH) in experimental studies and clinical observations in dose and/or time dependent exposure even when used within the clinically accepted doses. Recently, remifentanil has been used for pain management during anesthesia as well as in the intensive care units because of its rapid onset and offset. Objectives Search of the available literature to assess remifentanil AOT and OIH based on available published data. Methods We reviewed articles analyzing remifentanil AOT and OIH, and focused our literature search on evidence based information. Experimental and clinical studies were identified using electronic searches of Medline (PubMed, Ovid, Springer, and Elsevier, ClinicalKey). Results Our results showed that the development of remifentanil AOT and OIH is a clinically significant phenomenon requiring further research. Discussions and Conclusions AOT - defined as an increase in the required opioid dose to maintain adequate analgesia, and OIH - defined as decreased pain threshold, should be suspected with any unexplained pain report unassociated with the disease progression. The clinical significance of these findings was evaluated taking into account multiple methodological issues including the dose and duration of opioids administration, the different infusion mode, the co-administrated anesthetic drug’s effect, method assessing pain sensitivity, and the repetitive and potentially tissue damaging nature of the stimuli used to determine the threshold during opioid infusion. Future studies need to investigate the contribution of remifentanil induced hyperalgesia to chronic pain and the role of pharmacological modulation to reverse this process.